Lubuk Pahoman Streetscape Design Based on Lampung Saibatin Tribe Cultural Motifs - Priantara, Noviandes Dinasti; Franjaya, Eduwin Eko; Hutriani, Ina Winiastuti (Institut Teknologi dan Bisnis Ahmad Dahlan, 2026)
Since the Dutch East Indies colonial period, Teluk Betung Sub-district has played a significant role as an economic center and has been recognized as a historic old town in Lampung. In line with Sustainable Development Goal (SDG) 11.4 and Bandar Lampung City Regional Regulation No. 2 of 2019, preserving the historical character of the old city amid rapid modernization requires a culturally grounded streetscape design as a key expression of urban identity. Despite this potential, Teluk Betung faces several challenges, including the erosion of Lampung cultural identity due to transmigration, as well as disorganized spatial conditions such as street vendors occupying sidewalks and illegal parking along traffic lanes. This study aims to identify existing potentials and problems and to develop a culture-based streetscape design. The research adopts the landscape planning method proposed by LaGro (2008), encompassing the stages of preparation, inventory, analysis, synthesis, and concept development. The design proposal focuses on Way Lubuk Pahoman Street, where cultural principles are translated into a streetscape landscape concept, resulting in a site plan and three-dimensional visualization incorporating Lampung Saibatin cultural motifs.